Quality Factor of Planar Dipole in Two-Layer Infinite Phased Array - L. M. Liubina; M. I. Sugak (Известия высших учебных заведений России: Радиоэлектроника)
Quality factor formulas for planar dipole in two-layer infinite phased antenna array in case of lumped or spatial excitation are presented. The mathematical model is based on the integration near fields of elements within the Floquet cell. Results of the calculation of quality factor for different PAA geometry are presented.